2010
DOI: 10.5120/1106-1449
|View full text |Cite
|
Sign up to set email alerts
|

A Decision tree- Rough set Hybrid System for Stock Market Trend Prediction

Abstract: Prediction of stock market trends has been an area of great interest both to those who wish to profit by trading stocks in the stock market and for researchers attempting to uncover the information hidden in the stock market data. Applications of data mining techniques for stock market prediction, is an area of research which has been receiving a lot of attention recently. This work presents the design and performance evaluation of a hybrid decision tree-rough set based system for predicting the next days" tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 17 publications
0
32
0
3
Order By: Relevance
“…Later Wang in 2003 also utilized it in their work [16]. It was then proposed in the methodology by Nair et al in 2010 [17].…”
Section: Artificial Intelligence Systemsmentioning
confidence: 99%
“…Later Wang in 2003 also utilized it in their work [16]. It was then proposed in the methodology by Nair et al in 2010 [17].…”
Section: Artificial Intelligence Systemsmentioning
confidence: 99%
“…SVMs have also been successfully combined with decision trees (Nair et al, 2010b) for predicting stock market trends. A decision tree-rough set based stock market trend prediction system is presented in Nair et al (2010a). Adaptive filters have also been used for stock market prediction (Nair et al, 2010c).…”
Section: Introductionmentioning
confidence: 99%
“…The current day's trend, i.e., Up, down and no trend is determined according to Nair et al (2010aNair et al ( , 2010b in the following way:…”
Section: Introductionmentioning
confidence: 99%
“…Nair B.B. et al (2010) [6] suggested the design and performance evaluation of hybrid decision tree-rough set based system for predicting the next day's trend in the Bombay Stock Exchange (BSESENSEX).The proposed hybrid decision tree-rough set based trend prediction system produces better performance.…”
Section: Introductionmentioning
confidence: 99%